Low temperature co-fired ceramic packaging of CMOS capacitive sensor chip towards cell viability monitoring - Halonen, Niina; Kilpijärvi, Joni; Sobocinski, Maciej; Datta-Chaudhuri, Timir; Hassinen, Antti; Prakash, Someshekar B.; Möller, Peter; Abshire, Pamela; Kellokumpu, Sakari; Lloyd Spetz, Anita (Beilstein Journal of Nanotechnology, 2016)
Cell viability monitoring is an important part of biosafety evaluation for the detection of toxic effects on cells caused by nanomaterials, preferably by label-free, noninvasive, fast, and cost effective methods. These requirements can be met by monitoring cell viability with a capacitance-sensing integrated circuit (IC) microchip. The capacitance provides a measurement of the surface attachment of adherent cells as an indication of their health status. However, the moist, warm, and corrosive biological environment requires reliable packaging of the sensor chip. In this work, a second generation of low temperature co-fired ceramic (LTCC) technology was combined with flip-chip bonding to provide a durable package compatible with cell culture. The LTCC-packaged sensor chip was integrated with a printed circuit board, data acquisition device, and measurement-controlling software. The packaged sensor chip functioned well in the presence of cell medium and cells, with output voltages depending on the medium above the capacitors. Moreover, the manufacturing of microfluidic channels in the LTCC package was demonstrated.
Keywords: capacitance sensing; cell viability; lab-on-a-chip; low temperature co-fired ceramic (LTCC)